STUDI KOMPARASI INVESTASI UNITLINK DAN INVESTASI REKSADANA Studi pada High Net Worth Individual - , Dimas Gusta Nugraha ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The economic growth and development this time increasing both worldwide and domestic as well as increasing among HNWIs (High Net Worth Individuals). Insurance is also growing rapidly with the growth of the annual premium. insurance products was growing from protection to investment protection (unitlink). In this study will be compared if the investment in unitlink more attractive than other investments in this regard compared to mutual funds. This study also aims to provide advice to a HNWIs in selecting investments in accordance with the client's risk profile. This study uses 4 unitlink product samples and 5 samples mixed mutual funds. By looking at historical data for 5 years, the analysis used is a statistical t test with independent samples t test, and then use sensitivity analysis to determine the level of pessimistic, moderate and optimistic. The results showed that in the pessimistic state of unitlink greater return than mutual funds, while the state of standard and optimism returns from mutual funds is greater than the unitlink. So that clients are advised to choose mutual funds based on a moderate risk profile.